2012
DOI: 10.1021/es300126b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reaching the Targets of the Water Framework Directive in the Gulf of Finland

Abstract: This paper describes the development of the EU Water Framework Directive central water quality elements from 1970 to 2010 in the Gulf of Finland, a eutrophied sub-basin of the Baltic Sea. The likelihood of accomplishing the management objectives simultaneously is assessed using Bayesian networks. The objectives of good ecological status in winter-time total nitrogen and phosphorus, summer-time chlorophyll-a and summer-time Secchi depth have not been met yet. In addition, the results indicate that it is unlikel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Those authors pointed out that the majority of classifications in Europe are based on statistical approaches instead of ecological principles, thus the boundaries may not correspond to biologically meaningful changes in ecosystems. Further, Fernandes et al (2012) studied the probabilities to achieve the 'good' state for nutrients and chl-a in the GoF simultaneously, and concluded that the weak dependency between the studied metrics may result from a non-harmonised target-setting, which does not allow for dependencies, variability and uncertainty. Our results suggest that the inclusion of uncertainty in the present classifications may be justified.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors pointed out that the majority of classifications in Europe are based on statistical approaches instead of ecological principles, thus the boundaries may not correspond to biologically meaningful changes in ecosystems. Further, Fernandes et al (2012) studied the probabilities to achieve the 'good' state for nutrients and chl-a in the GoF simultaneously, and concluded that the weak dependency between the studied metrics may result from a non-harmonised target-setting, which does not allow for dependencies, variability and uncertainty. Our results suggest that the inclusion of uncertainty in the present classifications may be justified.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main explanations for this. For practical reasons, we have used the same transformation from chl- a to Secchi in all segments of the GoF area, whereas the exact form and strength of the dependence between these variables likely varies among and within the WFD areas (Fernandes et al 2012; Fleming-Lehtinen and Laamanen 2012). Another explanation may be that the WFD targets are relatively more stringent for chl- a than Secchi.…”
Section: Example Results and Pros And Cons Of The Bayesian Decision Mmentioning
confidence: 99%
“…In their review of assessment methods related to the WFD in Europe, Birk et al [10] pointed out that the majority of classifications are based on statistical approaches instead of ecological principles, thus the class boundaries may not correspond to biologically meaningful changes in ecosystems. Fernandes et al [11] used long term data to study the probability to achieve the 'good' state simultaneously for nutrients (phosphorus and nitrogen) and chlorophyll-a concentration in the context of WFD objectives at the Gulf of Finland, Eastern Baltic Sea, finding a weak dependency between these closely connected metrics. They concluded this finding may result from a non-harmonized target-setting, which does not take into account dependencies, variability and uncertainty.…”
Section: Aggregation Rules and The Risk Of Misclassificationmentioning
confidence: 99%